CCUS-assisted electricity-chemical polygeneration system for decarburizing coal-fired power plant: Process integration and performance assessment - Zhang, Leiyu; Tang, Zongyue; Gao, Ruxing; Wu, Ying; Wang, Lei; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng (Journal of Cleaner Production, 2024)
In the context of global carbon neutrality, carbon capture and storage (CCS) technology has become an important transition pathway to decarbonizing coal-fired power plants (CFPP). However, CCS technology has strict requirements for geological storage and the potential risk of CO2 leakage. Meanwhile, the deployment of the CCS technology in the CFPP could drastically reduce plant efficiency. To address the aforementioned issues, a novel carbon capture, utilization and storage (CCUS)-assisted electricity-chemical polygeneration process (i.e., ECPP) was proposed to produce electricity, liquid fuels, and high-calorie synthetic natural gas simultaneously. To reduce the efficiency loss caused by the consumption of internal steam and electricity, heat integration and Organic Rankine Cycle (ORC) technologies were adopted to fully recover the available waste heat and achieve the cascade utilization of the internal energy. Meanwhile, a detailed techno-economic assessment was conducted to further determine the benefits of the process integration. The results indicated that the application of heat integration and ORC technologies improves plant efficiency by 6 %. Moreover, it also reduces the cost of electricity and CO2 conversion cost by 17 and 15 %, respectively. In addition, compared with the traditional CFPPs retrofitted with CCS technology, the CO2 utilization and waste heat recovery technologies in ECPP enhance net electricity output and plant efficiency by 19 and 34 %, respectively. Therefore, the proposed CCUS-assisted ECPP achieves the efficient utilization of the waste CO2, and reduces the efficiency penalty for retrofitting the CFPPs. Overall, the proposed ECPP is an essential alternative for the retrofit of the existing CFPPs, and provides a feasible strategy for establishing a clean and sustainable power polygeneration system.
Keywords: Capture and storage technologies; Carbon storage; Carbon utilization; Coal-fired power plant; Efficiency penalty; Heat integration; Plant efficiency; Polygeneration system; Processes integrations; Techno-Economic analysis; CCUS; Coal-fired power plant; Efficiency penalty; Heat integration; Techno-economic analysis